Review Apartment by Consumer on Social Media vs Criminal Charges by Developer: Between Consumer Complaint and Defamation - Evi Kongres; Bariyima Sylvester Kokpan (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
Despite legal safeguards for freedom of expression and the right to be heard, consumers frequently encounter legal obstacles, particularly in cases where businesses initiate defamation claims. This issue is exemplified by the cases of Deedi Tjhandra, Muhadkly AT, and Desvalia, wherein consumers, after receiving no response to their complaints from developers, took to social media to post reviews of the apartment they had purchased. In these cases, it was found that the developers had breached contractual obligations, as the apartments and their associated amenities did not conform to the standards advertised in promotional materials. This study aims to analyze the rights of consumers to post video reviews of goods and/or services on social media, especially when such reviews result in defamation lawsuits and subsequent convictions. The court's ruling, in this case, found Deedi Tjhandra guilty of defamation despite the defamation statute in question having been repealed and replaced by more recent legislation. The updated legislation specifies that legal entities are barred from pursuing defamation claims. Additionally, the court did not consider the regulations established by the Joint Decree and CC rulings. The research employs a normative juridical methodology incorporating legislative and conceptual analyses. The novelty of this study lies in its exploration of the public interest concept within criminal and civil law as it pertains to defamation statutes being met through social media, particularly when these reviews serve the public interest. Additionally, the study assesses the adherence of law enforcement agencies to established regulations concerning defamation.